1959
DOI: 10.1128/jb.78.6.834-838.1959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Growth of Surviving Cells,

Abstract: In studies on the pasteurization of milk at ultra high temperatures it was observed that the surviving bacteria (less than 100 per ml) exhibited a prolonged lag phase during subsequent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1963
1963
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 3 publications
2
8
1
Order By: Relevance
“…From these experiments it appears that there is no relationship between the severity of the heat treatment and the fall in numbers occurring after inoculation and incubation in nutrient broth. This differs from the results of Kaufmann et al (1959) who, working with a heat resistant micrococcus, found that the lag phase increased from 22 to 40 h when the heat treatment was changed from 76" for 17 sec to 82" for 5 sec. These workers make no mention of a fall in numbers of heated cells after inoculation, but a study of their results indicates that a fall in numbers did occur in some cases.…”
Section: Discussioncontrasting
confidence: 99%
“…From these experiments it appears that there is no relationship between the severity of the heat treatment and the fall in numbers occurring after inoculation and incubation in nutrient broth. This differs from the results of Kaufmann et al (1959) who, working with a heat resistant micrococcus, found that the lag phase increased from 22 to 40 h when the heat treatment was changed from 76" for 17 sec to 82" for 5 sec. These workers make no mention of a fall in numbers of heated cells after inoculation, but a study of their results indicates that a fall in numbers did occur in some cases.…”
Section: Discussioncontrasting
confidence: 99%
“…3). This extended lag with heated cells is a frequently observed phenomenon (1, [3][4][5]8). During this extended lag, the cells completely recovered their tolerance to the EMB-NaCl medium and commenced to grow at a rate equal to that of normal cells and reached the same total viable population.…”
Section: Resultsmentioning
confidence: 90%
“…One such indication was obtained by studying the effect of actinomycin D on the growth of rehydrated, freeze-dried cells. Actinomycin D is a powerful inhibitor of deoxyribonucleic acid (DNA)-dependent RNA synthesis and is normally ineffective against E. coli (14). The lag time for freeze-dried cells in the presence of actinomycin D added at the start of incubation is extended to about 800 min.…”
Section: Injury To E Coli Caused Hy Freeze-dryingmentioning
confidence: 99%
“…Exposure of an organism to unfavorable environmental conditions or sublethal stresses, by either physical or chemical means, may result in physiological injury which is not immediately lethal. Subsequent treatment of such a cell, by supplying the proper nutrients or a more suitable environment, may afford the cell an opportunity of overcoming the injury and thus continuing as a viable organism. Injury has been demonstrated in cells exposed to heat (12)(13)(14), chilling or freezing (3,17,18,20,27,28), ionizing radiation (1,5), various chemicals (11), and to freeze-drying (10,23,24). Characteristics of injured organisms are an extended lag time, leakage of cellular materials (primarily nucleic acids), an increased sensitivity to selective media, and an increased nutritional requirement (12,13,17,18,20,23,(26)(27)(28).…”
mentioning
confidence: 99%